Examining the connection among national tourism expenditure and economic growth in Algeria - Salah Eddine Sari Hassoun; Khayereddine Salim Adda; Asma Hadjira Sebbane (Future Business Journal, 2021)
Tourism is one of the most important sectors for several researchers and decision makers, due to its influence on the world economic growth in the twenty-first century, making it as a source of competition between countries to a global industry for its effective strategic role in the development of countries. In this paper, we used two variables natural logarithm of per capita gross domestic product (GDP) and natural logarithm of per capita international and national tourism expenditure (ITE) to study the relationship between the tourism sector and economic growth in Algeria over the period of 1995-2017. We established with the unit root test with and without breakpoint that the variables are stationary in the first difference and there is a structural break in (ITE) and (GDP). Thus, with the presence of a breakpoint, we employed the methodology of Gregory-Hansen to avoid such issue, but we found that there was no evidence of cointegration with breakpoint, so then we used the vector autoregressive model (VAR). The model showed that the tourism sector has a positive and insignificant coefficient on the economic growth, while the economic growth factor has a positive and significant on the tourism sector. In the short run, there was a one-way causality from GDP to ITE at the level of 1%, confirming the economic-driven tourism growth hypothesis. Also, we found with Breitung and Candelon causality that there was same causality at the level of 10%.
Keywords: C19; L83; 650; Breitung and Candelon causality; Cointegration with breakpoint; Economic growth; Tourism; Unit root test with and without breakpoint